The Status of Women: Social and Religious Roles of Women in the Pre-Colonial Igbo Society - EDEMADU, Precious Chinecherem (Àgídìgbo: ABUAD Journal of the Humanities, 2025)
Igbo women at every historical juncture have played crucial roles, especially in the social and religious aspects of their various families, localities or communities. While they may not have held formal political titles in pre-colonial times, their influence reached far beyond the family space. They were caregivers, healers, matchmakers, and custodians of spiritual order. Indeed, they stood at the centre of rituals, ceremonies, and the moral life of the community. Karin Barber’s studies on African women, especially her work on Yoruba cultural practices, show how women often carry artistic and religious traditions. This study draws inspiration from her insights. However, it moves the discussion into the Igbo world, focusing on how artistic, social, and religious practices in Igbo society rested heavily on women both before and after colonial contact. Nevertheless, many practices survived, adapted, or merged with new realities. This study examines those changes. It explores how women maintained influence through religious duties, social alliances, and communal leadership even when formal authority structures changed. The goal is to highlight how their skills, traditions, and networks shaped Igbo society across different periods. The paper adopts qualitative historical methodology in conducting in-depth oral interviews, Focus Group Discussions, as well as content analysis based on data extracted from relevant literature. The findings demonstrate that revisiting women’s historical roles is crucial for shaping contemporary policies on gender, rights, and social development in Nigeria.